The effect of prepulse amplitude and timing on the perception of an electrotactile pulse - Favero, Jaspa; Luck, Camilla; Lipp, Ottmar; Marinovic, Welber (SPRINGER, 2024)
The perceived intensity of an intense stimulus as well as the startle reflex it elicits can both be reduced when preceded by a weak stimulus (prepulse). Both phenomena are used to characterise the processes of sensory gating in clinical and non-clinical populations. The latter phenomenon, startle prepulse inhibition (PPI), is conceptualised as a measure of pre-attentive sensorimotor gating due to its observation at short latencies. In contrast, the former, prepulse inhibition of perceived stimulus intensity (PPIPSI), is believed to involve higher-order cognitive processes (e.g., attention), which require longer latencies. Although conceptually distinct, PPIPSI is often studied using parameters that elicit maximal PPI, likely limiting what we can learn about sensory gating’s influence on conscious perception. Here, we tested an array of stimulus onset asynchronies (SOAs; 0–602 ms) and prepulse intensities (0–3× perceptual threshold) to determine the time course and sensitivity to the intensity of electrotactile PPIPSI. Participants were required to compare an ‘unpleasant but not painful’ electric pulse to their left wrist that was presented alone with the same stimulus preceded by an electric prepulse, and report which pulse stimulus felt more intense. Using a 2× perceptual threshold prepulse, PPIPSI emerged as significant at SOAs from 162 to 602 ms. We conclude that evidence of electrotactile PPIPSI at SOAs of 162 ms or longer is consistent with gating of perception requiring higher-level processes, not measured by startle PPI. The possible role of attentional processes, stimuli intensity, modality-specific differences, and methods of investigating PPIPSI further are discussed.